Application of Flue Gas Desulfurization Gypsum and Its Impact on Wheat Grain and Soil Chemistry. Issue 1 (1st January 2014) - DeSutter, T. M.; Cihacek, L. J.; Rahman, S.
Abstract : The 11 major electricity‐generating coal combustion stations in the northern Great Plains have the potential to produce almost 1 million Mg of flue gas desulfurization gypsum (FGDG) annually, which is a very attractive fertilizer (Ca and S) and amendment for sodic and acid soils. The potential environmental impacts of applying FGDG to soils in this region have not been fully investigated. The objectives of this research were to determine the influence of FGDG on soil chemical characteristics and to determine the impact that FGDG has on hard red spring wheat ( Triticum aestivum L.) yields and element analysis of the grain. Flue gas desulfurization gypsum and commercial gypsum were applied at rates of 0, 2.24, 11.2, and 22.4 Mg ha −1 to two soils in southwestern North Dakota in the spring of 2007. Soil and grain chemistries were monitored for two growing seasons. Wheat grain yields and elemental analysis of the grain were generally not affected by the gypsum treatments, indicating that the gypsum products did not negatively affect plant productivity. In addition, soil elemental analysis was similar across the treatments at both sites in both years. The results from this study indicate that its application to soil at rates used for sodic soil remediation (Mg ha −1 ) did not negatively affect the chemistries of either the soils or the wheat evaluated in this study compared with a commercial gypsum product or control soils.